The Role of Information Technology in Teaching English to Islamic Higher Education Learners: Assessing Digital Literacy Skills - Asmira, Mita (Nexus Publishing NXP, 2024)
The integration of Information Technology (IT) in English language teaching within Islamic higher education faces several challenges, particularly in developing comprehensive digital literacy skills among learners. Despite the growing reliance on digital tools, there remains a gap in students’ ability to effectively utilize these resources, especially in areas such as critical evaluation and ethical awareness. This study aims to assess the digital literacy competencies of 25 undergraduate students at Universitas Islam Internasional Darullughah Wadda’wah, focusing on their ability to navigate and employ IT in the context of English language learning. Using a 25-item close-ended questionnaire, the research evaluates five core dimensions: Technological Competence, Information Management, Critical Evaluation, Communication Proficiency, and Ethical Awareness. The findings reveal that while students demonstrate significant strengths in Communication Proficiency, there are critical shortcomings in Critical Evaluation and Ethical Awareness, highlighting the need for targeted interventions. These insights point to a broader issue of uneven digital literacy development, which poses a barrier to effective IT integration in language pedagogy. The study’s implications are multifaceted, suggesting that curriculum and instructional strategies should be adapted to address these gaps and promote a more balanced acquisition of digital skills. By aligning theoretical frameworks with practical applications, this research contributes to the discourse on enhancing digital literacy in Islamic higher education and calls for policy reforms that prioritize comprehensive digital literacy development.